A Gramsci’s Journey - Del Roio, Marcos [UNESP] (My University, 2022)
The journey towards the publication of Gramsci’s writings is well known, especially The Prison Notebooks. A journey that involved widespread disclosure of Gramsci’s name and work until he became the most renowned Italian author in the world. But this journey that has not yet reached completion and has only recently reached Africa and Asia, while reaches increased depth in Europe, North America and Latin America.